(untitled) (Jurnal Teknologi Industri Pertanian, 2016)
Enzymatic and acid microwave-assisted hydrolysis of a newly combined biological and microwave pretreatment was developed to evaluate the reducing sugar yield of betung bamboo fibers. In previous parallel study of single (biological or microwave) pretreatment, the improvement of reducing sugar yield of microwaveassisted acid hydrolysis has been reported previously. The cellulase of 10 and 20 FPU/g substrate was applied in the enzymatic hydrolysis of pretreated biomass using a shaking incubator at 50°C and 150 rpm for 48 hours. In the microwave-assisted acid hydrolysis, 1.0% sulfuric acid concentration was used either with or without the activated carbon aditionat microwave hydrolysisat 330 watt for 7.5-12.5 minutes. There was an improvement in reducing sugar yield of bamboo pretreated biological-microwave pretreatment after microwave assisted-acid hydrolysis compared to enzymatic hydrolysis. This hydrolysis performance improvement was greater than that of the single pretreatment (biological or microwave pretreatment). Bamboo pretreated by biological-microwave pretreatment (5% inoculum loading and irradiated for 5 minutes at 330 W) showed the highest reducing sugar yield after microwave hydrolysis for 12.5 minutes (16.65% per dry biomass or 18.92% per dry substrate). As much as 27.21% of hollocellulose can be converted to reducing sugar or 23.84% of theoritical maximum reducing sugar yield. The benefical effect of activated carbon addition in microwave assisted acid hydrolysis was the reduction of brown compound even though oligomer adsorption caused the decreasing of reducing sugar yield. Keywords: betung bamboo, brown compound, combination of biological and microwave pretreatment, enzymatic and acid-microwave hydrolysis, reducing sugar yield